Inspiration and Criticism: The Nineteenth-Century Crisis - Cameron, Nigel M. de S. (Tyndale bulletin, 1984)
The intellectual character of modern evangelicalism has, for better or worse, been decisively shaped by the nineteenth-century debates about the handling of the Bible.